2020
DOI: 10.2147/ijn.s217870
|View full text |Cite
|
Sign up to set email alerts
|

<p>In vitro Ultrasonic Potentiation of 2-Phenylethynesulfonamide/Magnetic Fluid Hyperthermia Combination Treatments for Ovarian Cancer</p>

Abstract: Background: Magnetic Fluid Hyperthermia (MFH) is a promising adjuvant for chemotherapy, potentiating the action of anticancer agents. However, drug delivery to cancer cells must be optimized to improve the overall therapeutic effect of drug/MFH combination treatments. Purpose: The aim of this work was to demonstrate the potentiation of 2-phenylethynesulfonamide (PES) at various combination treatments with MFH, using low-intensity ultrasound as an intracellular delivery enhancer. Methods: The effect of ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…5 and 6). The results indicated that magnetic hyperthermia improved the efficacy of chemotherapy, which could be due to the constructive effect of hyperthermia on the permeability of the cell membrane to the chemotherapeutic agents (Mérida et al 2020). The combinational treatment of MNPs and AMF hyperthermia resulted in more cytotoxicity than MNPs, and AMF alone (P < 0.05, Figs.…”
Section: Discussionmentioning
confidence: 88%
“…5 and 6). The results indicated that magnetic hyperthermia improved the efficacy of chemotherapy, which could be due to the constructive effect of hyperthermia on the permeability of the cell membrane to the chemotherapeutic agents (Mérida et al 2020). The combinational treatment of MNPs and AMF hyperthermia resulted in more cytotoxicity than MNPs, and AMF alone (P < 0.05, Figs.…”
Section: Discussionmentioning
confidence: 88%
“…First proposed by therapeutically by Gilchrist [281] in the 1950s, iron oxide nanoparticles provide localized heat sources for destroying diseased tissue [282] or dispersal of biofilms [283,284]. SPIONs in particular generate a significant amount of heat under an applied magnetic field (42-45 °C) [285] and have been used for cancer treatment through magnetic hyperthermia [286][287][288][289][290]. Taratula [291] recently developed magnetic nanoclusters composed of cobalt-and manganese-doped hexagonal iron oxide nanoparticles encapsulated in PEG-based polymer nanocarriers for hyperthermia treatment of ovarian cancer (Fig.…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…DOX-Fe 3 O 4 -TSL significantly inhibited tumor growth while causing no significant damage to normal tissues under NIR laser irradiation 101 . The combination of sonoporation and MH was proposed by Merida et al 102 . The authors used iron oxide NPs to induce MH and low-intensity US to enhance intracellular delivery during sonoporation.…”
Section: Magneto-ultrasonic Heatingmentioning
confidence: 99%